Sit-to-stand test as a complementary assessment in patients with cardiovascular disease - Avila-Valencia, Juan Carlos; Betancourt-Peña, Jhonatan; Saavedra Orozco, Nicol Andrea; Benavides-Cordoba, Vicente (Revista Cuidarte, 2026)
Highlights • The 1-Minute Sit-to-Stand Test (STS1) and the 6-Minute Walk Test (6MWT) involve simple, everyday movements and are well tolerated by patients. • The STS1 is a reliable, validated tool that is practical for clinical use in limited spaces. • As a functional assessment comparable to the 6MWT, the STS1 provides an effective option for monitoring physical status in patients with cardiovascular disease. • The STS1 assesses lower-extremity muscle strength, a key predictor of mortality in older adults. Introduction: The 1-Minute Sit to Stand Test (STS1) has gained relevance as a simple, safe, and functional test in patients with cardiovascular disease, especially in settings where the 6-Minute Walk Test (6MWT) is not feasible. Its usefulness in assessing lower- extremity muscle strength makes it a complementary tool of increasing interest that can strengthen functional assessment batteries in this population. Objective: To assess the correlation between the 6MWT and the STS1 as complementary tools in the functional assessment of patients with cardiovascular disease. Materials and Methods: Descriptive, correlational, cross-sectional study conducted in 45 patients enrolled in a cardiac rehabilitation program at a quaternary care clinic in Cali, Colombia. The 6MWT and STS1 were administered, assessing physiological variables and physical performance variables. Pearson’s correlation coefficient was used for bivariate analysis. Results: The mean age was 62.97 ± 12.58 years; 64.4% were women. Coronary artery disease was the most common diagnosis (73.3%). A moderate positive correlation was found between the distance walked in the 6MWT and the number of repetitions in the STS1 (r=0.610; p < 0.001). The 6MWT elicited a greater increase in heart rate (final: 112.7 ± 18.1), whereas the STS1 had a greater impact on systolic blood pressure (final SBP: 146.8 ± 27.9; p < 0.001). Discussion: The results are consistent with studies in other populations and support the use of STS1 as a valid functional assessment option. Conclusion: The STS1 complements the 6MWT in the functional assessment of patients with cardiovascular diseases. How to cite this article: Ávila-Valencia Juan Carlos, Betancourt-Peña Jhonatan, Saavedra-Orozco Nicol Andrea, Benavides-Cordoba Vicente. Sit-to-Stand test as a complementary assessment in patients with cardiovascular disease. Revista Cuidarte. 2026;17(2):e4864. https://doi.org/10.15649/cuidarte.4864